Short-term effects of covid-19 on physical performance, training load and mental health — a study of Chinese young well-trained sprint kayakers - Deng, S.; Li, Y.; Deng, J.; Yin, M.; Chen, Z.; Nassis, G, (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: COVID-19 has a complex impact on multiple body systems affecting both physical performance and mental health [1]. Evidence-based information on the effects of COVID-19 on athletes` performance can help towards safe return-to-play protocols and clinical management strategies [2]. This study aims to examine the short-term effects of COVID-19 on physical performance, training load, and mental health in young well-trained sprint kayakers during the 2022-2023 season. METHODS: 17 kayakers (8 male,9 female, age 17.5 ± 1.6 yrs, height 176.03 ± 7.02 cm, body mass 68.8 ± 10.0 kg; mean±SD) underwent two upper-body strength tests and anthropometric measurements before (2 weeks) and after a mild COVID-19 infection (up to 2 weeks after retraining). Mild COVID-19 infection was defined as being without hospitalization and without any health complications lasting longer than 14 days [3]. Peak and mean power output (PP and MP), peak and mean propulsion velocity (PV and MV), and 40-s maximal repetitions of bench pull and bench press were measured with a linear transducer (Gymaware) before and after COVID-19. CR-10 session rating of perceived exertion (sRPE) for training load and Hooper questionnaire for mental status were measured daily and averaged weekly. Nose swab PCR/antigen tests for COVID-19. Statistical analysis included the use of Wilcoxon signed rank test, Student t-test, Pearsons and Spearmans r correlation coefficients. RESULTS: Duration of main symptoms, detraining, and retraining was 2.9 ± 1.1, 10.4 ± 1.8, and 12.1 ± 1.1 days. There was a significant improvement in body mass, fat-free mass, muscle mass, flexed biceps circumference, absolute and relative PP, and MP of bench pull before and after COVID-19 (p < 0.05). There was a significant reduction in training hours per week, sRPE, sRPE-TL, fatigue levels, muscle soreness levels, and Hooper index before and after COVID-19 (p < 0.05). However, the duration of main symptoms and detraining were negatively correlated with PP, MP, and PV of bench press after COVID-19 [range r = -0.51 (p < 0.05) to r = -0.67 (p < 0.01)]. Duration and training hours per week of retraining were positively correlated with body mass, fat-free mass, muscle mass, flexed biceps circumference, PP, MP, PV, and MV of bench pull and bench press [range r = 0.50 (p < 0.05) to r = 0.73 (p < 0.001)]. Sleep quality, stress, fatigue, muscle soreness levels, and Hooper index during the retraining period were negatively correlated with PP and MP of bench pull and bench press [range r = -0.48 (p < 0.05) to r = -0.85 (p < 0.001)]. CONCLUSION: A mild COVID-19 infection resulted in changes of anthropometric, training, mental health, and performance variables, but did not result in a reduction of physical performance in well-trained young athletes after short-term retraining. The results of this study will provide valuable information to inform clinical management and improve return-to-play protocols.